Walter Quintin Gresham papers - Gresham, Walter Quintin, 1832-1895.
Correspondence, telegrams, newspaper clippings, printed matter, and other papers relating chiefly to Gresham's service as U.S. postmaster general in the administration of Chester Alan Arthur, U.S. secretary of state in the administration of Grover Cleveland, and as a judge. Includes Gresham's Civil War letters to his wife, Matilda Gresham, written from camps near Corinth and Vicksburg, Miss.; Kenesaw Mountain, Ga.; Memphis and Shiloh, Tenn.; and Paducah, Ky. Subjects include Indiana state and national politics, the Louisiana lottery, judicial matters, the presidential elections of 1884 and 1888, the annexation of Hawaiian, and pelagic sealing in the Bering Sea.
Correspondents include Thomas F. Bayard, Erastus Brainerd, Benjamin Harris Brewster, Benjamin Helm Bristow, Martin L. Bundy, Noble Chase Butler, Grover Cleveland, David Davis, Charles Denby, Thomas Drummond, Charles E. Dyer, Henry Wood Elliott, John Watson Foster, Robert Sanford Foster, John Marshall Harlan, R.M. Kelly, Elijah Bishop Martindale, Joseph Medill, John Tyler Morgan, John Overmyer, Julian Pauncefote, James M. Scovil, Thomas C. Slaughter, David W. Voyles, Henry Watterson, Albert S. Willis, J.H. Woodard, and Gresham's son, Otto Gresham.
Microfilm edition of containers 39-43 and 48 available
Microfilm produced by Library of Congress Photoduplication Service from originals in the Manuscript Division.
U.S. secretary of state, secretary of the treasury, postmaster general, jurist, statesman, and soldier.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arthur, Chester Alan, -- 1829-1886.; Bayard, Thomas F. -- 1828-1898 -- Correspondence; Brainerd, Erastus, -- 1855-1922 -- Correspondence; Brewster, Benjamin Harris, -- 1816-1888 -- Correspondence; Bristow, Benjamin Helm, -- 1832-1896 -- Correspondence; Bundy, Martin L., -- 1817 or 1918-1910- -- Correspondence; Butler, Noble Chase, -- 1844-1933 -- Correspondence; Cleveland, Grover, -- 1837-1908.; Cleveland, Grover, -- 1837-1908 -- Correspondence; Davis, David, -- 1815-1886 -- Correspondence; Denby, Charles, -- 1830-1904 -- Correspondence; Drummond, Thomas, -- 1809-1890 -- Correspondence; Dyer, Charles E., -- 1834- -- Correspondence; Elliott, Henry Wood, -- 1846-1930 -- Correspondence; Foster, John Watson, -- 1836-1917 -- Correspondence; Foster, Robert Sanford, -- 1834-1903 -- Correspondence; Gresham, Matilda, -- 1839- -- Correspondence; Gresham, Otto, -- 1859-1946 -- Correspondence; Harlan, John Marshall, -- 1833-1911 -- Correspondence; Kelly, R. M. -- 1836- -- Correspondence; Martindale, Elijah Bishop, -- 1828-1910 -- Correspondence; Medill, Joseph, -- 1823-1899 -- Correspondence; Morgan, John Tyler, -- 1824-1907 -- Correspondence; Overmyer, John, -- 1844-1919 -- Correspondence; Pauncefote, Julian, -- Baron, -- 1828-1902 -- Correspondence; Scovil, James M. -- Correspondence; Slaughter, Thomas C. -- Correspondence; Voyles, David W. -- Correspondence; Watterson, Henry, -- 1840-1921 -- Correspondence; Willis, Albert S. -- 1843-1897 -- Correspondence; Woodard, J. H. -- Correspondence; United States. -- Army; United States. -- Department of State; United States. -- Post Office Department; Law -- United States; Lotteries -- Louisiana; Presidents -- United States -- Election -- 1884.; Presidents -- United States -- Election -- 1888.; Sealing -- Bering Sea; Corinth (Miss.) -- History; Georgia -- History -- Civil War, 1861-1865.; Hawaii -- Annexation to the United States; Hawaii -- Politics and government -- 1893-1900.; Indiana -- Politics and government; Kennesaw Mountain (Ga.) -- History; Kentucky -- History -- Civil War, 1861-1865.; Memphis (Tenn.) -- History; Mississippi -- History -- Civil War, 1861-1865.; Paducah (Ky.) -- History; Shiloh (Tenn.) -- History; Tennessee -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 19th century; United States -- History -- Civil War, 1861-1865.; Vicksburg (Miss.) -- History; Cabinet officers; Jurists; Soldiers; Statesmen